Representation of Chinese Culture in the Animation Film I Am What I Am 1: Semiotic Study《我就是我 1》动画片中中国文化的表征: 符号学研究 “Wǒ jiùshì wǒ 1” dònghuà piàn zhōng zhōngguó wénhuà de biǎozhēng: Fúhào xué yánjiū - Ririn Ayu Indah Manalu; Alemina Br. Perangin-angin; Jessy (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to analyze the representation of Chinese culture in the animated film I Am What I Am 1 directed by Sun Haipeng using Roland Barthes’ semiotic approach. The research employed a descriptive qualitative method through documentation studies of scenes, symbols, and character interactions that represent elements of Chinese culture. Data were analyzed based on three levels of meaning: denotation, connotation, and myth. The findings reveal that Chinese culture is represented through various cultural symbols, including lanterns, red envelopes (angpao), traditional musical instruments, qipao, the Chinese character fu (福), lion dance (barongsai), and the lion symbol. These symbols embody values such as hope, prosperity, social solidarity, courage, and cultural preservation. The film functions not only as a medium of entertainment but also as an effective tool for cultural representation and education, introducing Chinese cultural values to a wider audience.